Photosynthetic and transcriptome responses to fluctuating light in Arabidopsis thylakoid ion transport triple mutant - Gollan Peter J.; Grebe Steffen; Roling Lena; Grimm Bernhard; Spetea Cornelia; Aro Eva-Mari (Wiley, 2025)
Fluctuating light intensity challenges fluent photosynthetic electron transport in plants, inducing photoprotection while diminishing carbon assimilation and growth, and also influencing photosynthetic signaling for regulation of gene expression. Here, we employed in vivo chlorophyll-a fluorescence and P700 difference absorption measurements to demonstrate the enhancement of photoprotective energy dissipation of both photosystems in wild-type Arabidopsis thaliana after 6 h exposure to fluctuating light as compared with constant light conditions. This acclimation response to fluctuating light was hampered in a triple mutant lacking the thylakoid ion transport proteins KEA3, VCCN1, and CLCe, leading to photoinhibition of photosystem I. Transcriptome analysis revealed upregulation of genes involved in biotic stress and defense responses in both genotypes after exposure to fluctuating as compared with constant light, yet these responses were demonstrated to be largely upregulated in triple mutant already under constant light conditions compared with wild type. The current study illustrates the rapid acclimation of plants to fluctuating light, including photosynthetic, transcriptomic, and metabolic adjustments, and highlights the connection among thylakoid ion transport, photosynthetic energy balance, and cell signaling.